2015
DOI: 10.1590/0001-3765201520130351
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Cyclosporin A and Heteropterys tomentosaon the rat liver

Abstract: Cyclosporin A (CsA) is a widely employed immunosuppressive drug that is associated with several side effects, among then hepatotoxicity. Heteropterys tomentosa is a Brazilian plant efficient in reducing damage caused by CsA on the rat testis and prostate. The aim of this study was to evaluate the effect of CsA and H. tomentosa (administered isolated or simultaneously) on the liver of Wistar rats. The animals were treated daily with water (control), CsA (15mg/kg/day), H. tomentosa infusion or CsA+H. tomentosa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Furthermore, previous studies reported that the utilisation of cyclosporine A harmed testicular function, causing sperm counts, sperm motility and fertility to decline (Gawish et al, 2016; Monteiro, Predes, Matta, & Dolder, 2008; Srinivas et al, 1998). The main mechanism that underlies most of the cyclosporine‐induced toxicities is reported to be the generation of oxygen free radicals (De Freitas et al, 2015). Cyclosporine A induced structural and functional toxicity in the testicular tissue via oxidative stress mechanisms (Türk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies reported that the utilisation of cyclosporine A harmed testicular function, causing sperm counts, sperm motility and fertility to decline (Gawish et al, 2016; Monteiro, Predes, Matta, & Dolder, 2008; Srinivas et al, 1998). The main mechanism that underlies most of the cyclosporine‐induced toxicities is reported to be the generation of oxygen free radicals (De Freitas et al, 2015). Cyclosporine A induced structural and functional toxicity in the testicular tissue via oxidative stress mechanisms (Türk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Results opposite to those of Galvão et al (2011) on the learning and memory of rats were reported by Paula-Freire et al (2013) during an 80-day treatment with the hydroethanolic extract of the H. tomentosa roots, as well as no evidence of an adaptogenic effect. De Freitas (2015) also reported hepatotoxicity on oral administration (75.76 mg/kg) of the aqueous infusion of H. tomentosa in rats treated for 21 days.…”
Section: Introductionmentioning
confidence: 91%
“…These medicines are used in combined therapy, usually as a complex of three different drugs, following kidney transplantation. C by binding cyclophilin inhibits calcineurin and therefore leads to decreased interleukin-2 transcription and thus deactivates T cells [7]. It can be replaced by Tc, which acts differently in an initial pathway, as Tc binds to FK506.…”
Section: Introductionmentioning
confidence: 99%
“…E exhibits antineoplastic and antiproliferative properties such as inhibiting fibroblast proliferation and fibrosis, but it also inhibits replication of the hepatitis C virus (HCV) [5]. Mycophenolate mofetil is an immunosuppressive drug acting by inhibition of inosine monophosphate dehydrogenase and thus selectively inhibits lymphocyte proliferation [7]. From above-mentioned drugs E and MMF are contraindicated during pregnancy [5].…”
Section: Introductionmentioning
confidence: 99%